Pengaruh Kualitas Pelayanan dan Kepercayaan terhadap Keputusan Menggunakan Layanan KSP Pamuji: Studi Kasus Soloraya (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the effect of service quality and trust on members’ decisions to use the services of Koperasi Simpan Pinjam (KSP) Pamuji in the Soloraya region. Savings and loan cooperatives play an important role in providing financial access for the community; therefore, service quality and members’ trust are crucial factors in sustaining cooperative services. This research employs a quantitative approach with an explanatory research design. Data were collected through a structured online questionnaire distributed to 201 respondents selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 27. The results indicate that service quality has a positive and significant effect on service usage decisions, as evidenced by a regression coefficient of 0.504 and a significance value below 0.05. Trust also shows a positive and significant effect on service usage decisions with a regression coefficient of 0.375. Simultaneously, service quality and trust explain 82.5% of the variation in service usage decisions. These findings confirm that positive service experiences and high levels of trust are key determinants in encouraging members to use cooperative savings and loan services. The results of this study are expected to provide practical insights for cooperative managers in formulating strategies to improve service quality and strengthen members’ trust in order to enhance sustainability and competitiveness.